KEMAMPUAN ADSORPSI KITOSAN UNTUK ION LOGAM TIMBAL (Pb2+) DAN KADMIUM (Cd2+) - John Hendri; Rahmawati -; Aspita Laila (Universitas Andalas, 2008)
ABSTRACT Chitosan is natural polymer that has been known to posses the capacity to adsorb various transition metals. This capacity of adsorption is resulted from the ability of chitosan to form complex compound with metal, especially Pb and Cd. The formation of chitosan-metal complex is enabled by the presence of active hydroxil group in chitosan molecule. The results of this study on adsorption of Pb2+ and Cd2+ revealed the existence of linear relationship between the amount of the metal adsorbed with concentration of the metal tested. It was found that for Pb2+, the maximum adsorption was 10.32 mg/g which was achieved for the metal concentration of 50 mg/L, and 24.998 mg/g for Cd2+ at metal concentration of 100 mg/L. The optimum contact time for adsorption was found to be 24 hours for both metals. The adsorption was found to take place with the adsorption energy of 29.82 kJ/mol for Pb2+ and 17.23 kJ/mol for Cd2+. Keywords: chitin, chitosan, adsorption, transition metal, and toxic metal